Pengawasan Realisasi Belanja Sosial APBN Melalui Pendekatan Social Watch (Socwatch) - Vianida Hardiningsih; Muhammad Arief Nugroho (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
General welfare and social justice are the main ideals of the Indonesian nation as mandated by the 1945 Constitution and Pancasila. In an effort to realize this, the government allocates funds through the State Budget (APBN) for social protection programs (perlinsos). However, the implementation of perlinsos often faces various challenges, such as inaccurate targeting, budget misuse, and duplication of assistance. This problem shows the need for a more effective and transparent monitoring mechanism to ensure the optimization of social spending realization. Through the SocWatch concept, a comprehensive web application for monitoring the realization of APBN social spending with financial data analytics and machine learning technology, this method is able to identify anomalous patterns, detect potential deviations, and present data in a visual format that is easily accessible to the public. The interactive reporting feature in SocWatch allows the public and stakeholders to actively participate in supervision and follow-up. This solution is expected to strengthen transparency, accountability, and collaboration between the government and the public in managing state finances. In addition, SocWatch has the potential to be a strategic tool in supporting efforts to prevent corruption, accelerate economic transformation, and encourage the realization of targeted social spending for equitable welfare in Indonesia.